Performance of Protective Clothing: Fourth Volume 1992
DOI: 10.1520/stp19200s
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Mannequin Evaluation of Thermal Protective Clothing

Abstract: An instrumented mannequin has been constructed for testing the thermal protective qualities of garments when subjected to short duration flash fires. To measure the rate of heat transfer to the mannequin surface 110 skin simulant sensors are used. The flash fires are produced with propane diffusion flames. A computer controlled data acquisition system is used to run the experiment, record and store the data, calculate the extent and nature of skin damage and display the results. The sampling rate of the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 2 publications
1
20
0
1
Order By: Relevance
“…The experiments were conducted at relatively low pressures compared to industrial settings where the typical steam pressure existing in lines for the day-to-day operations can be up to 620 kPa. In the current research it was observed that for all three fabrics the sensor temperature rose above 50 °C under most conditions, implying second-degree burn to the skin tissue [15], and could be much worse if the exposure time is higher.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The experiments were conducted at relatively low pressures compared to industrial settings where the typical steam pressure existing in lines for the day-to-day operations can be up to 620 kPa. In the current research it was observed that for all three fabrics the sensor temperature rose above 50 °C under most conditions, implying second-degree burn to the skin tissue [15], and could be much worse if the exposure time is higher.…”
Section: Discussionmentioning
confidence: 57%
“…Nine skin simulant sensors based on that developed by Dale, Crown, Ackerman, et al [15] were placed on the front surface of the cylinder to measure the heat transfer through fabrics. The sensors were a 19-mm-diameter, 32-mmthick plug of colerceran with a 30-gauge copper constantan thermocouple bonded to the surface to measure surface temperature.…”
Section: Type Of Temperature Sensormentioning
confidence: 99%
“…In particular, regulations should address the magnitude and changing character of the motor vehicle fire problem by developing fire performance (fireworthiness) requirements for motor vehicles that will guarantee sufficient time for escape or rescue from a post-crash fire. Supporting standards should be developed based on human tolerance to the effects of fire, heat (as heat release is the most important factor in fire hazard [40]), smoke and toxic gases (especially carbon monoxide), which are well defined [24] and easily measured [24,41,42]. To have a meaningful effect on post-crash survivability, fireworthiness standards will guarantee that passengers find survivable conditions until rescue crews can arrive, in the event of restricted egress or incapacitation.…”
Section: Discussionmentioning
confidence: 99%
“…그들은 피부손상은 화학반응에 의해 발생 하는 것으로 표현할 수 있고, 따라서 1차 Arrhenius 화학 반응속도 방정식을 이용하여 조직 손상의 시간변화율에 대해 다음과 같이 제안하였다. Torvi and Dale (16) Xu et al (17) Dale et al (18) Thickness of layer (m) Table 2의 열물성치 모델들을 이용하여 계산을 수행하였 으며, Stoll and Chianta (9) 의 2도 화상에 대한 실험 결과와 비교하여 Figure 5에 나타내었다. 그림에서처럼 대부분의 열물성치 결과들에 대하여 Stoll and Chianta (9) 의 실험결과를 비교적 잘 예측함을 알 수 있 다.…”
Section: 초기조건unclassified